Measurement Scales in Natural Language. Issue 1 (January 2015) - Solt, Stephanie
Abstract The meaning of a wide variety of natural language expressions can be stated in terms of degrees on scales. This paper provides an overview of the contribution of scales to linguistic meaning. I discuss the ontology of scales, survey the role of scalarity within and across languages, and summarize recent research into the linguistically relevant features of scales, organizing these findings into a preliminary framework for a comprehensive model of scale structure. The relation between the scales underlying the interpretation of gradable expressions and those involved in the calculation of scalar implicatures – so‐called Horn scales – is also briefly discussed.